The Effect of Foot Exercise Therapy on Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus - Ari Wibowo, Thomas; Dwiastuti, Anita (LPPM STIKes Muhammadiyah Ciamis, 2024)
Diabetic foot exercise aims to improve blood circulation, strengthen muscles, prevent deformities, and overcome joint motion limitations. After doing foot exercise therapy, it can be seen changes in the patient's blood sugar levels, whether blood sugar levels return to normal and can be overcome. Purpose: This research was conducted in the form of a literature review. Methode: This research method is library research, which is a series of studies related to the method of collecting library data or researching and using library information (scientific journals) for the object of research.. Result : This study has found 10 research articles based on the following journal databases, namely Researchgate, Google Schoolar, Scinences Direct that there is an effect of foot exercise therapy on reducing blood sugar levels in patients with type 2 diabetes mellitus. Conclusion: From 10 research journals, it was concluded that 10 journals reported the effect of giving foot exercise therapy on reducing blood sugar levels in Type 2.